Fique (Furcraea macrophylla) overturning and its agronomic repercussions - Ortiz-González, Daniel (Agronomía Mesoamericana, 2022)
Introduction. Overturning is known as plant downfall, a phenomenon that affects the yield and quality of harvests in various crops. In Colombia, overturning has been evidenced in fique (Furcraea spp.) plantations, but its effects have been little studied. Objective. To determine overturning repercussions on fique plant growth and fiber production. Materials and methods. Twenty upright plants and twenty plants with overturning were evaluated under a completely randomized design in a forty-year-old crop in Totoro, Cauca, Colombia in March 2021. Growth, yield, and fiber length (LF) were evaluated. Additionally, the percentage of overturning and mortality was quantified through a random sampling of 166 plants. Results. The incidence of overturning was 58 %, of the overturned plants 23 % died due to stem rot. The overturning affected growth, reducing stem diameter (DT), leaf length (LH), leaf width (AH), total number of leaves (NTH) and the leaf length and width ratio (RLA) by 10, 23, 14, 39, and 10,5 %, respectively, compared to upright plants. Likewise, fiber length and yield decreased by 24 and 56 %, respectively. Conclusions. The overturning caused a greater affectation in fiber production than the reported by the macana virus, the most limiting disease of the crop. These findings highlighted the importance of seeking and implementing management strategies as a contribution to the sustainability of the chain in the country.